THEORETICAL BASIS OF USING METHODOLOGICAL CONTROL TOOLS IN AN ADAPTIVE ENTERPRISE MANAGEMENT SYSTEM - TYURINA, Nila; PESHKOVA, V. (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The essence, features, relevance, components of the adaptive enterprise management system and their interrelationships are formulated. The conditions for the need to transition to adaptive enterprise management are determined. Adaptive indicators include value and cost criteria for the efficiency of enterprise activities. The introduction of controlling as an adaptive management tool into the enterprise management system is justified. An analytical study of the substantive essence of the category of "controlling" was conducted by foreign and domestic scientists using informational, coordination and performance approaches. The author’s definition of "controlling" was formulated as a concept of managing the future state of an enterprise in adaptive conditions, as an integrated digital system. The information and accounting component are considered as the basis of the controlling system, which serves as the main source of all data in analytical sections. Monitoring of the functioning of the enterprise as a key element of controlling is substantiated. Author’s interpretations of its essence are considered and the relationship of these categorical concepts in the process of enterprise management is traced. Monitoring is identified as an important information and analytical base for preparing management decisions, the stages of its implementation, modification and structural models are considered. A substantive description of the theoretical basis of the controlling system is formed. The tools and forms of controlling within its components are considered in detail: strategic analysis, management monitoring, business diagnostics. Approaches to building a controlling model in the format of adaptive management theory are analyzed. The main methodological tools of controlling have been formed, which can be used in the navigational and adaptive concept with a focus on value-oriented enterprise management.